Analysis of Critical Criteria for Assessment of Logistics Service Provider Company (Case Study: PT. Pos Logistik Indonesia) - Suzana, Yenny; Irwansyah, Budi; Suparni, Suparni; Darmawan, Wanda (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
The quality of services provided by logistics providers has a direct impact on an organization's business. Organizations need to critically evaluate the performance of their LSPs and choose service providers rationally. LSPs understand the importance of service quality to their survival and growth and strive to provide high-quality services. PT Pos Logistik Indonesia (PLI) is a company that operates in the field of Logistics Delivery Services which can include documents, electronic products, logistics, and others.  PT Pos Logistik Indonesia (PLI) in Langsa City should have criteria as a logistics service provider to ensure customer satisfaction. This research aims to analyze these criteria through a survey collected from 120 Small and Medium Enterprises (SMEs) organizations in Langsa City that use the services of PT Pos Logistik Indonesia (PLI). Small and Medium Enterprises (SMEs) are individual business entities or legal entities that have small initial capital, or a small value of wealth (assets) and a small (limited) number of employees. Questionnaire strategies were used to identify criteria selection-based sustainable logistics service quality (SLSQ) theoretical framework, that is sustainable transport elements, training, collaboration, sustainable packaging, and sustainable information. The explanatory factor analysis method was employed. The top three ranked criteria for evaluating logistics service provider criteria selection based on sustainable logistics service quality are the trained PLI employees, the sustainable packaging, and the commitment to environmental goals. Through this research, it confirms that sustainable logistics practices can bring value to PLI as LSPs and better improve their performance and customer satisfaction.